Microbial dysbiosis in a mouse model of atopic dermatitis mimics shifts in human microbiome and correlates with the key pro‐inflammatory cytokines IL‐4, IL‐33 and TSLP. (22nd January 2022) - Amar, Y.; Schneider, E.; Köberle, M.; Seeholzer, T.; Musiol, S.; Hölge, I.M.; Gschwendtner, S.; Krappmann, D.; Steiger, K.; Biedermann, T.; Schmidt‐Weber, C.B.; Alessandrini, F.
Abstract: Background: Cutaneous bacterial dysbiosis is a characteristic hallmark of atopic dermatitis (AD), and it decisively influences the severity of the disease. Despite this, frequently used murine models of AD have not been characterized regarding the changes in skin microbiome communities. Objective: To analyse the skin microbiome of two frequently used murine models for AD for assessing their applicability in translational research. Methods: AD was induced in mice by topical application of calcipotriol or oxazolone. Following comparable elicitation of AD‐like dermatitis, including IgE induction, the skin microbial communities were analysed and compared with human AD. Results: We detected critical differences in the microbiota composition of diseased skin. In contrast to calcipotriol treatment, application of oxazolone induced significant changes in the cutaneous microbiota and a drastic drop of bacterial richness. Furthermore, an expansion of Staphylococci, particularly S. xylosus, was observed in the oxazolone group, also displaying positive correlations with AD key markers including pH, TEWL, IL‐4, TSLP and IL‐33. Conclusions: In this article, we show that (a) the model of choice to investigate AD needs to be characterized for the cutaneous microbiota if applicable and (b) the oxazolone‐mediated mixed Th1‐Th2 immune response triggers microbiota‐induced alterations which share similarities to dysbiosis in human AD and represents therefore a suitable model for translational research on AD if alterations of the microbiome are in the focus of the investigation.